2011
DOI: 10.1007/s10111-011-0192-5
|View full text |Cite
|
Sign up to set email alerts
|

Haptic shared control: smoothly shifting control authority?

Abstract: Literature points to persistent issues in humanautomation interaction, which are caused either when the human does not understand the automation or when the automation does not understand the human. Design guidelines for human-automation interaction aim to avoid such issues and commonly agree that the human should have continuous interaction and communication with the automation system and its authority level and should retain final authority. This paper argues that haptic shared control is a promising approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
292
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(303 citation statements)
references
References 34 publications
9
292
1
1
Order By: Relevance
“…Sliding scale autonomy [20] relaxes discrete LOA to a continuum of assistance. Additionally, prevailing shared control approaches such as potential field methods [2], virtual fixture based methods [25], [1], and haptic shared control [14] are ultimately rooted in LOA/FA. For example, in [28], the optimal controller of a cart-pendulum task was used in conjunction with a haptic interface to filter suboptimal user input (the machine decided when to give assistance).…”
Section: Related Workmentioning
confidence: 99%
“…Sliding scale autonomy [20] relaxes discrete LOA to a continuum of assistance. Additionally, prevailing shared control approaches such as potential field methods [2], virtual fixture based methods [25], [1], and haptic shared control [14] are ultimately rooted in LOA/FA. For example, in [28], the optimal controller of a cart-pendulum task was used in conjunction with a haptic interface to filter suboptimal user input (the machine decided when to give assistance).…”
Section: Related Workmentioning
confidence: 99%
“…Trust issue has to do with relatively long-term use of the system (Abbink et al, 2012). Trusting the operation of the system is directly related to the adoption of system by the human agent.…”
Section: Human Factor Issues Of the Shared Control Systemmentioning
confidence: 99%
“…Understand category means that how much human can easily and intuitively understand the operating principle of the system (Abbink et al, 2012;Akamatus et al, 2013;Billings, 1997;Bruemmer et al, 2002;Hoc, 2001). Various problems are able to arise when the human agent does not understand the machine agent properly from the perspective such as capabilities, boundaries of operation, current functionality or goals (Abbink et al, 2012).…”
Section: Human Factor Issues Of the Shared Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to overcome the out-of-the-loop problem is to apply the haptic shared control concept [7], where the human and the automation "share" the control device (steering wheel in this case). Research has shown that shared control is better than hands-off automated driving for a driver to maintain his/her sit- * Advanced Safety System Development DiV.…”
Section: Introductionmentioning
confidence: 99%